Study of urinary uric acid and creatinine ratio as a marker of neonatal asphyxia for babies born in a tertiary care hospital - Krishnana, Elango; Ponnusamy, Venmugil; Sekar, Sathiya Priya (International Journal of Research in Medical Sciences, 2017)
Background: Perinatal asphyxia is a common neonatal problem and there is significant contribution to neonatal morbidity and mortality. It is regarded as an important and common cause of preventable cerebral injury. The prediction of perinatal asphyxial outcome is important but formidable. There is only a limited role for the Apgar score for predicting the immediate outcome, such as HIE and the long-term neurological sequelae observational error can happen in APGAR. But biochemical parameters can be truly relied upon. This study was to evaluate the utility of urinary uric acid to creatinine ratio (UA/CR ratio) as non-invasive, easy, cheap and at the same time early biochemical means of asphyxia diagnosis. Methods: In this prospective case control study conducted in KAPV Government medical college between Feb 2017 to Sept 2017, 100 asphyxiated and 100 non-asphyxiated newborns were included. Detailed history and assessment were for all the enrolled newborns. Spot urine samples were sent for uric acid and creatinine estimation. Results were recorded, and statistical analysis was done. Results: The mean Uric acid/Creatinine ratio in the cases and controls groups were 2.58±1.09 and 0.86±0.17 respectively. The ratio also correlated well with the stage of HIE. Conclusions: The ratio of UA/Cr enables early and rapid recognition of asphyxial injury and also the assessment of its severity and the potential for short term morbidity or death.